Analisis Kualitas Air pada Mata Air di Desa Galao, Kecamatan Loloda Utara, Kabupaten Halmahera Utara - Buka, Oktosea; Lotono, Mutia; Yusniar, Masitah; Janis, Harsen Berg; Boleu, Fiktor Imanuel; Akyuwen, Frandy (Physikos: Journal of Physics and Physics Education, 2025)
Water plays an important role in human life, and one of the water resources that can be a source of clean water is groundwater or what is also called a spring. Therefore, the spring in Galao Village, North Loloda District, North Halmahera Regency, needs to be maintained and cared for. In this study, researchers tested water content using several parameters, namely hardness, TDS (Total Dissolved Solids), DHL (Electrical Conductivity), turbidity, and pH. The results of sample testing carried out in two laboratories showed a turbidity of 1.00 NTU and a pH of 7.145 which were tested at the North Halmahera Regency Environmental Service Laboratory. Meanwhile, the main parameters of hardness were recorded at 231 mg/l, TDS 391 mg/l, and DHL 521 μS/cm which were tested at the Manado Industrial Standardization and Service Center (BSPJI) Laboratory. Physically, the three main parameters, namely hardness, TDS and DHL are interrelated; Hardness is caused by contact between water and limestone in the soil layer through which water passes, allowing calcium (Ca) and magnesium (Mg) to dissolve into it. In line with the cause of the presence of dissolved substances caused by weathering, dissolution of rocks and soil and other organic and inorganic substances dissolved in water, there is a relationship between Electrical Conductiv ity (ECP) and the ions contained therein, ions in water come from dissolved salts of alkali compounds, chloride sulfide dissolved in water. The purpose of this study is to determine the content of Hardness, Total Dissolved Solids (TDS), Electrical Conductivity (DHL), Turbidity, and pH contained in water.